2020
DOI: 10.20944/preprints202011.0422.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health Status of University Healthcare Workers During the COVID-19 Pandemic: A Post-Movement Lockdown Assessment

Abstract: This study investigated the prevalence and severity of depression, anxiety, and stress and determined the association between various factors, social support, and depression and anxiety among university healthcare workers in Malaysia after the government lifted the movement control order (MCO) put in place to curb the coronavirus disease 2019 (COVID-19) pandemic. This online, cross-sectional survey recruited 399 participants from two university hospitals, and they were administered a self-reported questionnair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
5
15
3
1
Order By: Relevance
“…The prevalence of stress in this study was in line with the studies conducted in China 56.59%. 6 On the other hand, our estimation was higher than the studies conducted in Spanish 41.1%, 23 India 3.7%, 25 Singapore 6.6%, 13 Turkey 41.2% 30 and Malaysia 29.1%, 28 while the magnitude of stress was lower than studies conducted in China 71.5%, 8 18.0%, 9 Turkey 76.4%, 29 and Alberta Canada 85.6%. 27 This could be the sample size difference, the health system service difference.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The prevalence of stress in this study was in line with the studies conducted in China 56.59%. 6 On the other hand, our estimation was higher than the studies conducted in Spanish 41.1%, 23 India 3.7%, 25 Singapore 6.6%, 13 Turkey 41.2% 30 and Malaysia 29.1%, 28 while the magnitude of stress was lower than studies conducted in China 71.5%, 8 18.0%, 9 Turkey 76.4%, 29 and Alberta Canada 85.6%. 27 This could be the sample size difference, the health system service difference.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study, the magnitude of depression was consistent with the study conducted in Libya 56.3%. 5 On the other hand, the prevalence of depression on health-care workers was higher than the studies conducted in China 44.37%, 6 12.2%, 7 50.4%, 8 15.4%, 9 40%, 22 Spanish 46%, 23 systematic review studies 22.8%, 12 21.7%, 24 India 11.4%, 25 Singapore 8.9%, 13 Nepal 8%, 26 Alberta Canada 44.0%, 27 Malaysia 21.8%, 28 whereas the prevalence of depression in this study was lower than studies done in Turkey 77.6%, 29 64.7%. 30 The reason for this discrepancy might be, the simple size difference, the time of research done.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The prevalence of risk of depression was found to be 67.1% in anesthetists from a Malaysian COVID-19 referral hospital [ 31 ]. In other studies, the prevalence rates ranged from 11.1% to 31.6% for anxiety and from 9.9% to 21.8% for depression [ 32 , 33 ]. Only large-scale data involving local, non-frontline university populations are currently available [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 95%
“…Physicians described both senior and junior colleagues as an important source of social support [ 31 ]. Several studies demonstrated social support to be a protective factor for mental health during the COVID-19 pandemic for HCWs in Asia [ 32 , 33 , 34 ]. As cultures differ between continents and countries [ 35 , 36 ], the perception, manifestation, or protective role of social support might also.…”
Section: Introductionmentioning
confidence: 99%